2018
DOI: 10.1080/09546634.2018.1441492
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of methotrexate versus interferon in cutaneous T-cell lymphomas

Abstract: The most significant finding of this study was that patients with CTCL treated with IFN had a better response rate and significantly shorter response time compared with those treated with MTX. Additionally, patients had less disease progression on IFN than with MTX regardless of subtype of T-cell lymphoma and stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
2
9
1
1
Order By: Relevance
“…Interestingly, the TTR was significantly shorter in the IFN-α group than in the MTX group (1 month vs. 2 months). Responses to both IFN-α and MTX were achieved 1 month earlier compared to the results published by Wain et al [9]. The reasons for differences in TTR and RR between our trial and the Wain et al study are unclear [9].…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Interestingly, the TTR was significantly shorter in the IFN-α group than in the MTX group (1 month vs. 2 months). Responses to both IFN-α and MTX were achieved 1 month earlier compared to the results published by Wain et al [9]. The reasons for differences in TTR and RR between our trial and the Wain et al study are unclear [9].…”
Section: Discussioncontrasting
confidence: 40%
“…The major side effects of IFN-α treatment are dose-dependent and include flu-like symptoms, elevated transaminases, myelosuppression, and depression. INF-α has proven to be effective in MF and SS treatment, both as monotherapy and in combination with oral retinoids, bexarotene, or PUVA therapy [4][5][6][7][8][9][10][11][12]. The few studies assessing the use of IFN-α monotherapy in CTCL demonstrated that partial response was achieved in 25% to 49% of patients [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐dosed methotrexate (MTX; 5 to 25 mg/week) is recommended for stage IIB or higher. It may be used as monotherapy or combined with bexarotene or IFNα2b [ 82 , 94 ]. Intravenous chemotherapy, as monochemotherapy with pegylated liposomal doxorubicine or gemcitabine, is recommended for patients in the tumor stage with visceral involvement, for treatment of refractory/recurrent disease, or for “debulking” (reduction of tumor burden, a priori).…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Deshalb wird eine Kombination von IFNα2b mit Retinoid für Patienten bei unzureichendem Therapieerfolg in der Monotherapie empfohlen oder wenn eine Kombination mit PUVA kontraindiziert oder nicht verfügbar ist[82]. Niedrig dosiertes Methotrexat (MTX; 5 25 mg/Woche) wird ab IIB empfohlen und kann als Mono-oder Kombinationstherapie mit Bexaroten oder IFNα2b verabreicht werden[82,94]. Eine intravenöse Chemotherapie wird bei Patienten im Tumorstadium, mit viszeraler Beteiligung, bei therapierefraktärerer/rezidivierender Erkrankung oder für Debulking (Tumorlastreduktion, a priori) als Monochemotherapie mit pegyliertem liposomalen Doxorubicin oder Gemcitabin empfohlen.…”
unclassified